Computational study on radical-mediated thiol-epoxy reactions - KAHRAMAN, MEMET VEZİR (My University, 2023)
Radical-mediated thiol-epoxy reactions were elucidated for analyzing the overlap problem of the thiol–ene/thiol–epoxy systems using computational approaches. Nine epoxy model molecules were evaluated to mimic the chemical structures and reactivity of some industrial epoxy molecules. Modeling reaction mechanisms was conducted through density functional theory (DFT) calculations using the M06-2X/6-31+G(d,p) level at 1.0 atm and 298.15 K. An analog thiol–ene mechanism was proposed for radical-mediated thiol–epoxide reactions. Unlike the thiol–ene reactions, the addition reaction to epoxides is relatively slow (rate constants <10–4 M–1 s–1). However, the chain transfer, which paves the way for the overlapping of dual curing systems, is quite fast (rate constants >101 M–1 s–1). High stability of thiyl radicals, epoxy ring strain, and the instability of formed alkoxy radical from addition reaction were emphasized as the main driving forces for the reaction energetics and kinetics. Control of temperature and using certain thiols are strongly recommended to avoid curing step overlap based on the findings in this study.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Addition reactions; Molecular modeling; Molecules; Organic polymers; Thiols